(untitled) (Journal of Informatics and Mathematical Sciences, 2010)
In the paper [3] we defined three new classes of sequences motivated by the Logarithm Rest Bounded Variation Sequences defined by S.P. Zhou [4]. By means of these classes we extended Zhou’s theorems pertaining to L^1-convergence of sine series. Very recently R.J. Le and S.P. Zhou [1] proved L^1-approximation theorems. Now we generalize their theorems to our wider classes.